Intraoperative glycaemic control in Non insulin dependent Diabetes Mellitus: a comparison between normal saline and ringer’s lactate - IM Sulaiman; HS Lee; S Balan; MZ Jaafar (Penerbit UKM, 2006)
Fifty Non Insulin Dependent Diabetes Mellitus (NIDDM) patients undergoing surgery under epidural anaesthesia were studied. All patients received dextrose 5% infusion at 100 ml/hr from the period of fasting until upon arrival to the operation room. Patients were randomly divided into two groups. Patients in Group 1 (n=25) received normal saline while patients in Group 2 (n=25) were given Ringer’s lactate. Both groups received their infusion throughout the operative period up to four hours postoperatively. Blood glucose level was measured at baseline, 45 minutes intra operatively and postoperatively at 30 minutes and four hours by using a glucometer. Patients in Group 2 has a larger mean increase in blood glucose level of 1.5 mmol/L between 4 hours postoperatively and baseline compared to 0.96 mmol/L inGroup 1. However, this was not statistically significant. There was no difference in the increase of mean glucose level at 30 minutes when compared to baseline. There was a significant increase in mean blood glucose level in both groups in the postoperative period when compared to baseline. This study demonstrated that patients with NIDDM receiving Ringer’s lactate has a larger increase in mean blood glucose level compared to those receiving normal saline, but the magnitude is not statistically significant